Significance of Immune and Non-Immune Cell Stroma as a Microenvironment of Hepatocellular Carcinoma—From Inflammation to Hepatocellular Carcinoma Progression - Baj, Jacek; Kołodziej, Magdalena; Kobak, Joanna; Januszewski, Jacek; Syty, Kinga; Portincasa, Piero; Forma, Alicja (International journal of molecular sciences, 2024)
Hepatocellular carcinoma (HCC) is the most common liver cancer as well as the most prevalent cause of death in the adult patient population with cirrhosis. The occurrence of HCC is primarily caused by chronic liver inflammation that might occur because of a viral infection, non-alcoholic fatty liver disease (NAFLD), or various lifestyle-associated factors. The objective of this review was to summarize the current knowledge regarding the microenvironment of HCC, indicating how immune- and non-immune-cell stroma might affect the onset and progression of HCC. Therefore, in the following narrative review, we described the role of tumor-infiltrating neutrophils, bone-marrow-derived cells, tumor-associated mast cells, cancer-associated fibroblasts, tumor-associated macrophages, liver-sinusoidal endothelial cells, lymphocytes, and certain cytokines in liver inflammation and the further progression to HCC. A better understanding of the HCC microenvironment might be crucial to introducing novel treatment strategies or combined therapies that could lead to more effective clinical outcomes.